Flexible and Accessible Automated Operation of Miniature Chromatography Columns on a Liquid Handling Station. Issue 3 (5th December 2017) - Konstantinidis, Spyridon; Goh, Hai‐Yuan; Martin Bufájer, José M.; de Galbert, Paul; Parau, Maria; Velayudhan, Ajoy
Abstract : The High Throughput (HT) investigation of chromatographic separations is an important element of downstream bioprocess development due to the importance of chromatography as a technique for achieving stringent regulatory requirements on product purity. Various HT formats for chromatography exist, but the miniature column approach has characteristics resembling large scale packed bed column chromatography the most. The operation of such columns on robotic stations can be automated, but this is not always a straightforward procedure; the robotic manipulations are highly dependent on the settings of each experiment and the standard commands of the supporting software may not provide readily the required flexibility and accessibility for "plug and play" functionality. These can limit the potential of this technique in laboratories engaging on HT activities. In this work, we present an application which aims to overcome this challenge by providing end‐users with a flexible operation of the miniature column technique on an automated liquid handler. The application includes a script which is written on Freedom EVOware, and is supplemented by custom compiled executables. Here, the manipulations carried out by the application are described in detail and its functionality is demonstrated through typical experiments based on bind and elute miniature column chromatography. The application is shown to allow for the unsupervised "on‐the‐fly" programming of the robotic station and to ultimately make the technique accessible to non‐automation experts. This application is therefore well suited to simplifying development activities based on the robotic deployment of the miniature column chromatography technique. Abstract : Miniature columns are suitable for downstream bioprocessing activities. However, their deployment requires expertise in robotic programming. Here, an application is described aiming to reduce this technique to a routinely deployed tool. It employs an advanced script, and custom executables, converting user inputs to robotic instructions and operations, and ultimately, processed results, in a fully unsupervised fashion. These make the technique accessible to non‐automation experts, enhance its high throughput nature, and serve to unlock its potential for bioprocess development.